Building and sustainability information modeling: An analysis of its thematic structure - Gutiérrez, Alejandro Roberto Issais; Espinosa, Julio Cesar Martínez (Iberoamerican Journal of Science Measurement and Communication, 2024)
Objective. This study examines bibliographic production that addresses the intersection between building information modeling (BIM) and sustainability, considering business, academic, and scientific perspectives. The main objective is to analyze the relationship between BIM and sustainability to contextualize their development in these fields. Design/Methodology/Approach. A search was conducted in the Scopus database using the keywords "building information modeling" and "sustainability". The VOSviewer bibliometric tool was selected for thematic analysis, combining co-word analysis and the h-index. This methodology enabled the effective visualization of diagrams and thematic areas in all available publications. Results/Discussion. Four thematic groups were identified: new technologies and their applications, sustainable construction, sustainability and energy efficiency, and life cycle and environment management. A trend towards greater integration and synergy between BIM and sustainability was evident. The five main research lines around these topics were presented and discussed, which were: development of sustainability assessment methodologies based on BIM, optimization of the life cycle of buildings through BIM, innovation in sustainable materials and technologies, modeling of the resilience and adaptability of buildings, and standards and regulations for sustainability in BIM. Conclusions. The future is oriented towards BIM and sustainability due to their capacity to optimize construction efficiency, reduce waste, and promote sustainable practices.